A study on the hot workability of a novel TNM-RE alloy (RE = Y, La, Ce) - Zhanxing Chen; Tengfei Ma; Qiuwei Xing; Guoju Li; Xinzhe Zhang; Xinfang Zhang (Materials Research Express, 2023)
The hot deformation behavior of a novel TNM-RE alloy (RE = Y, La, Ce) was studied using a hot simulation machine (Gleeble-3800), and microstructural evolution was also characterized. Finally, 3D forging was carried out on isothermal forging equipment. It is shown that the as-cast lamellar colony size is about 20 ∼ 30 μ m, which is refined by the formation of rare Earth oxides and borides at grain boundaries inhibiting grain growth. The peak stress of the TNM-RE alloy deformed at 1200 °C/0.01 s ^−1 is about 97 MPa, which is governed by the lamellar colony size and the B2 phase. Based on microstructure observation, it is found that the lamellar is bent and elongated to coordinate plastic deformation, where dynamic recrystallization nucleates preferentially, and full dynamic recrystallization is obtained at 1220 °C/0.01 s ^−1 . The TNM-RE alloy was forged by 3D isothermal forging method, and fine grains with a size of 10 ∼ 20 μ m were obtained by controlling the process parameters. The novel TNM-RE alloy shows an excellent hot workability.